Riverfront found: weaving together a complex fabric of past, present, and future on the mighty Mississippi - Enroth, Chris (Kansas State University, 2010)
Many small Midwestern towns established near a river thrived on industry and the transport of goods up and down the waterway. Unfortunately, industrial riverfronts that have acted as the heart of their communities have seen tremendous flux as time has progressed. In the past half century the economic activity of industrial riverfronts declined as more goods can be shipped via interstate highways and as factories are closed and relocated. These vacant factories leave behind contaminated brownfield sites which discourage reinvestment and promote greenfield development on a city’s periphery in agricultural lands. Citizens have turned their backs on a history and heritage from which the first cornerstones of their communities were laid. A void results as industry begins to fade from the riverfront and a town loses its connection to the river. Put simply, we have lost our riverfronts. The Riverfront Found Master Plan for Quincy, Illinois integrates the different uses of the riverfront, weaving together the existing industrial, recreational, and natural fabrics that line the Mississippi River. Design concepts strive to create a dynamic atmosphere to encourage a healthy lifestyle environment and destinations with year-round interest. Enjoyable and memorable experiences of Quincy’s riverfront encourage users to return as the negative community perceptions of the Mississippi River are reversed. Planning is inwardly focused to combat sprawl of the urban fabric. Decision-making remains sensitive to floodplain ecology and mindful of flood occurrence. Conservation is an important design response concerning riverfronts and requires understanding an intricate system regionally and locally. Education ties both conservation and site experience together as users remember how their city and culture are embedded in ecology. Three case studies identify key concepts to inform the project at later stages. A site inventory and analysis spanning three scales, regional, city, and site uncovers history and processes. The programming phase addresses proposed elements to address the concepts, ideas, and problems identified in previous steps. A final master plan presents the proposed program elements within context of the site to create a functional and dynamic riverfront for the citizens of Quincy.
Keywords: Landscape architecture; Mississippi River; Riverfront; Quincy, Illinois; Landscape Architecture (0390); Urban and Regional Planning (0999)